The Organization’s Commitment Modernizes the Competence of Human Resources and Leadership Style on the Quality of Financial Statements in the TTU - Desmon Redikson Manane; Aquidowaris Manek (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The aims of this research is to know the partial effect from the competence of Human Resources Development (X1, ) Leadership Style (X2) for the Quality of Financial Statements (Y),  the partial effect  among the competence of Human Resources (X1), leadership style (X2); Commitment organization (X3) for the quality of financial statement; Human Resources competence (X1) and style leadership (X2) for the organization commitment (X3); Effect of Human resources for financial statement quality (Y) that moderation by organization commitment (X1) dan the effect of leadership style for the quality of financial statement (Y) that moderated by organization commitment (X3). The Result showed that competence variable SDM (X1) was not affected for the commitment organization (X3) whereas leadership style (X2) was affected by organization commitment for the quality of financial statement (Y) The Competence of human resources variable (X1), leadership style and organization commitment (X3) were not moderating among the effect of human resources competence (X2) for the quality of financial statement as well as the effect of leadership style (X2) to Financial statement (Y). If it was comparted, the direct effect from human resource for the quality financial statement there was more if when it was moderated by organization commitment. The same way what happening for the effect of leadership style for the quality of financial statement. The information which given from this research can be used to increase the human resources competence by financial management and applicating the good leadership style and more careful the quality financial statement.